2021
DOI: 10.2147/ijgm.s331611
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Oral Manifestations in Symptomatic Non-Hospitalized COVID-19 Patients: A Cross-Sectional Study on a Sample of the Saudi Population

Abstract: Purpose Few case reports and letters to the editor have been published regarding oral signs and symptoms in COVID-19 patients. The aim of the study therefore is to investigate different types of oral manifestations in COVID-19 patients as well as their prevalence. Patients and Methods The study is a cross-sectional study from a single medical center. A convenience sample was taken from all patients who were COVID-19 confirmed, symptomatic, and non-hospitalized. Demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
12
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
5
12
0
2
Order By: Relevance
“…Nonetheless, we were able to establish a link between the presence of oral manifestations and the presence of specific general symptoms of COVID-19. Similar to other cohorts studied in Saudi Arabia, most of the participants in our study described the general symptom of a chemosensory disorder, such as the loss of smell and taste, as being severe and extending for more than 5 days [ 28 ]. Loss of taste along with anosmia was concurrent and attributed to edema of the respiratory system [ 6 ].…”
Section: Discussionsupporting
confidence: 67%
“…Nonetheless, we were able to establish a link between the presence of oral manifestations and the presence of specific general symptoms of COVID-19. Similar to other cohorts studied in Saudi Arabia, most of the participants in our study described the general symptom of a chemosensory disorder, such as the loss of smell and taste, as being severe and extending for more than 5 days [ 28 ]. Loss of taste along with anosmia was concurrent and attributed to edema of the respiratory system [ 6 ].…”
Section: Discussionsupporting
confidence: 67%
“…Alteration in the quantity and composition of saliva can lead to gustatory dysfunction. Loss of taste was also reported by Natto et al 11 & Amorim Dos Santos J et al 5 Anemia related to SARS-CoV-2 mediated hemolysis also causes the oral manifestations. ACE2, CD147, and CD26 receptors present on the erythrocytes are potential targets for SARS-CoV-2 attachment, which can lead to hemolysis.…”
Section: Discussionsupporting
confidence: 57%
“…Alteration in the quantity and composition of saliva can lead to gustatory dysfunction. Loss of taste was also reported by Natto et al11 & Amorim Dos Santos J et al5 Anemia related to SARS-CoV-2 mediated…”
supporting
confidence: 63%
“…Intriguingly, several investigators have reported numerous orofacial manifestations of SARS-CoV-2 infection including taste and smell disturbances, xerostomia, salivary gland disorders, and mucosal lesions. [1][2][3][4][5][6][7][8] In an extensive review of patients admitted to hospital, Orilisi et al [9] have reported that oral ulcers, cheilitis, and tongue lesions were more common before hospitalization, while perioral pressure ulcers, macroglossia, blisters, and oral candidiasis were more frequent during hospitalization of COVID-19 patients.…”
mentioning
confidence: 99%
“…However, studies that have assessed orofacial manifestations in active COVID-19 patients are hampered due to the risk of infection transmission. In a pioneering study, Natto et al, [7] using a convenience sample of 109 COVID-19 patients, have reported that loss of taste was the most common oral manifestation, followed by desquamated gingivitis, coated tongue, and ulceration. Furthermore, Villarroel-Dorrego et al [12] have reported that altered taste and a painful/burning mouth were common symptoms among 55 COVID-19 patients in Venezuela.…”
mentioning
confidence: 99%